2011
DOI: 10.1002/nau.21007
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic nervous system hyperactivity in early streptozotocin‐induced diabetic kidney disease

Abstract: The data demonstrate an early role for the renal sympathetic innervation in the pathogenesis of DKD. If the kidney is prevented from renal sympathetic nerve action renal functional parameters are markedly improved. The data further suggest an early enhancement in renal sensitivity to intrarenal norepinephrine (NE) upon the removal of renal sympathetic tone in STZ-induced diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recently it was suggested that renal sympathetic innervation plays a role in the pathogenesis of diabetic nephropathy implying early enhancement in renal sensitivity to intrarenal norepinephrine on diabetic renal injury [ 15 ]. Since STZ-diabetes requires several months to determine structural autonomic denervation of the gastrointestinal tract [ 16 ] and of the heart [ 17 ], and no data are available on renal denervation induced by diabetes, we propose surgical renal denervation in SHR injected with STZ to evaluate the effects of renal denervation on cardiovascular reflexes and markers of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was suggested that renal sympathetic innervation plays a role in the pathogenesis of diabetic nephropathy implying early enhancement in renal sensitivity to intrarenal norepinephrine on diabetic renal injury [ 15 ]. Since STZ-diabetes requires several months to determine structural autonomic denervation of the gastrointestinal tract [ 16 ] and of the heart [ 17 ], and no data are available on renal denervation induced by diabetes, we propose surgical renal denervation in SHR injected with STZ to evaluate the effects of renal denervation on cardiovascular reflexes and markers of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Ang-II exerts complex hemodynamic and nonhemodynamic actions which contribute to DN, namely, induction of systemic vasoconstriction, increased glomerular arteriolar resistance and capillary pressure, increased glomerular capillary permeability, reduction in the filtration surface area, stimulation of ECM proteins, and renal proliferation [1416]. It is also an important regulator of fluid and electrolyte balance, stimulates aldosterone production, activates the sympathetic nervous system, and increases sodium reabsorption [17, 18]. …”
Section: Approaches To the Treatment Of Dnmentioning
confidence: 99%
“…[ 10 ] In the present case, due to the long-term complication of diabetes mellitus, the patient's renal autonomic nervous system was thought to be overactivated. [ 11 ] In addition, similar to the findings observed in unilateral renal artery stenosis, [ 12 ] unilateral ureteral obstruction stimulates renin secretion from obstructed kidneys and thus activates the renin-angiotensin system. [ 4 ] Consequently, in the present case, such neural and humoral abnormalities may have caused reflex vascular constriction and ureteral spasm in the contralateral kidneys.…”
Section: Discussionmentioning
confidence: 67%